Effects of aging on vocal function: A systematic review - Moreira, Victor Hugo Tetilla; Esposito, Mario Pinheiro; Xavier, Tarcisio Redes; Ferrer, Rayna Gonçalves; Esposito, Izabela Pinheiro; Ferreira, Thales Victor Fernandes; Santos, Karina Alencastro dos (Seven Editora, 2023)
Introduction: Aging is a natural and inevitable process that affects all areas of the body, including vocal function. The voice plays an important role in communicating and expressing emotions. A variety of physiological and biomechanical changes can impair vocal function with aging. In view of the above, this study is justified by its academic, scientific, and social relevance, with the aim of exploring in detail the effects of aging on vocal function, including associated structural and physiological changes and their social and emotional implications. Objective: To demonstrate, through the scientific literature, the effects of aging on vocal function. Methodology: This is a systematic review research, carried out according to the indications of the PRISMA method. Data collection took place in the scientific bases: LILACS, SCIELO and MEDLINE. Results and Discussion: The discussion about the effects of aging on vocal function is crucial for us to understand how the natural aging process affects such a fundamental aspect of human communication. It was evidenced through the analysis of the selected sample, the main aspects for the present discussion. The natural aging of the voice occurs progressively in parallel with other bodily functions and is influenced not only by the anatomy and physiology of the body, but also by the lifestyles that individuals lead throughout their lives. Conclusion: Understanding the effects of aging on speech function has advanced significantly, but knowledge gaps still need to be filled. More research is needed to validate the effectiveness of different therapeutic interventions and to develop innovative approaches to facilitate voice quality improvement in older adults. DOI:https://doi.org/10.56238/sevened2023.004-047